Bean breeding - National Bean Programme (National Bean Programme, 1990)
A plant breeding program was developed, consisting of the following stages: (1) hybridization for disease resistance; (2) adaptation trial, and (3) screening for resistance. Several variations of Isariopsis griseola existing in Malawi as well as sources of resistance to this fungus were identified in local bean germplasm. Variation was observed in adaptation and disease resistance to angular leaf spot, common blight, BCMV, web blight, and rust. The highest yielding genotypes were also the most resistant: A 286 (508 kg/ha), A 344 (438), and BAT 477 (417). Pathogenic variation was observed for Isariopsis griseola (10 isolates) and sources of resistance to this pathogen were found. Bean genotypes PI 167399, Coco ala Creme, and G 05434 were resistant to all the isolates of the pathogen, the smallest lesions being observed in G 05434. (CIAT)